Strengthening Character Values in Class VII History Learning Through Sukuh Temple Relief Architecture - Fainanu Zuhaida; Rosita Dwi Rahmawati; Dany Miftah M. Nur (JURNAL PENDIDIKAN IPS, 2024)
This study aims to determine the value of what character values are contained in the relief architecture of Sukuh Temple which can be used as a reinforcement of character education in historical learning. This study aims to describe various kinds of character values contained in the reliefs of Sukuh Temple and their relevance as character strengthening in historical learning. To achieve this goal, the author uses qualitative research methods and field studies including data collection using direct observation techniques and supported by literature sources including journals, scientific reports, theses, and related articles as well as data analysis using qualitative descriptive analysis. The results showed that Sukuh Temple has architecture with reliefs including Garudeya, Horseshoe, and Sudamala reliefs. These reliefs have historically contained meaning and contain character values. Those character values can be a reinforcement of character to be implemented in learning through history learning. These values include religious character, tolerance, discipline and responsibility, hard work, independence, and self-sacrifice.